Are you on Timeline or News Feed? The roles of Facebook pages and construal level in increasing ad effectiveness. (April 2016) - Kim, Dong Hoo; Sung, Yoon Hi; Lee, So Young; Choi, Dongwon; Sung, Yongjun
Abstract: This study examines how psychological distance between a user and a Facebook page (Timeline vs. News Feed) impacts the effectiveness of advertising messages framed by two different construal levels (high- vs. low-level construal). Based on construal level theory, a 2 (Psychological distance: distant vs. proximal) × 2 (Message type: high-level vs. low-level construals) factorial design was employed. The results of the study showed that individuals accessing the News Feed page responded more favorably to abstractly framed desirability-focused messages than concretely framed feasibility-focused messages. In contrast, individuals accessing the Timeline page showed more positive reactions to concretely framed feasibility-focused messages compared to abstractly framed desirability-focused messages. The study concludes with the discussions of theoretical and empirical implications and recommendations for future research. Highlights: Individuals have different psychological distances toward their Facebook pages (Timeline & News Feed). Individuals' social relationship in Facebook influences the psychological distance toward the pages (Timeline & News Feed). The psychological distances influence the effectiveness of messages in those Facebook pages (Timeline & News Feed).